"ОРЗИГУЛ" ДОСТОНИ МАТНИНИНГ ФОНЕТИК ХУСУСИЯТЛАРИ - Хаджимусаева, Н.Н. (SCIENCE and SOCIETY, 2016)
The article deals with the phonetic peculiarities of the text in the epic poem “Orzigul”. The author studies the falling and changes of sounds and dialectal peculiarities in the epos in accordance with the literary norms.